Safety, Tolerability and Pharmacokinetics of Intravenous Sodium Taurodeoxycholate, HY209, a GPCR19 Agonist Inhibiting Inflammasomal Activation - Chung WK; Jeon I; Jang IJ; Seong SY; Han SA; Yu KS (Drug Design, Development and Therapy)
Woo Kyung Chung,1 Inseung Jeon,1 In-Jin Jang,1 Seung-Yong Seong,2 Seon Ae Han,3 Kyung-Sang Yu1 1Department of Clinical Pharmacology and Therapeutics, Seoul National University College of Medicine and Hospital, Seoul, Republic of Korea; 2Department of Biomedical Sciences, Seoul National University College of Medicine, Seoul, Republic of Korea; 3Shaperon Inc, Seoul, Republic of KoreaCorrespondence: Kyung-Sang Yu, Department of Clinical Pharmacology and Therapeutics, Seoul National University College of Medicine and Hospital, 101 Daehak-ro, Jongno-gu, Seoul, 03080, Republic of Korea, Tel +82 2 3668 7833, Fax +82 2 742 9252, Email ksyu@snu.ac.krBackground: HY209 is a synthesized sodium taurodeoxycholate (TDCA) that is expected to serve as a novel treatment for sepsis by inhibiting the inflammasomal activation that suppresses the production of pro-inflammatory cytokines. This study aimed to assess the safety, tolerability and pharmacokinetics (PKs) of HY209 after intravenous administration in healthy subjects.Methods: A dose-block randomized, double-blind, placebo-controlled, single ascending dose study was conducted. Eight subjects in each dose group were randomized to receive an intravenous administration of HY209 (0.1, 0.2, 0.4, 0.8 and 1.6 mg/kg) or a placebo at a 3:1 ratio. Safety and tolerability variables including adverse events (AEs) and vital signs were monitored. For the PK analysis, serial blood samples were collected for 72 hours at baseline and up to 24 hours post-dose. A power model was used to evaluate the dose-proportionality of HY209. Given that TDCA is an endogenous compound, time-matched baseline differences in plasma concentrations were analyzed.Results: A total of 39 subjects completed the study. All AEs were mild, and no serious AEs were observed. There was no significant correlation between the frequency of AEs and the administered dose. A circadian pattern was observed in the plasma TDCA concentration at baseline. After infusion, the plasma TDCA was rapidly eliminated; the plasma TDCA concentration at one hour after the end of infusion showed no significant differences from the baseline. The baseline-adjusted maximum plasma concentration of TDCA demonstrated dose-proportionality in a HY209 range of 0.1– 1.6 mg/kg.Conclusion: A single intravenous administration of HY209 was well tolerated and its systemic exposure showed dose-proportionality in a dose range between 0.1 and 1.6 mg/kg.Keywords: phase I clinical trial, pharmacokinetics, sepsis, bild acid